Development of Canva Interactive Media in Pancasila Education Learning Using Problem Based Learning (PBL) Model for Grade V Elementary Schools - Kurnia, Anggun; Reinita, Reinita; Waldi, Atri; Nisa, Sahrun (FKIP - Universitas Riau, 2025)
This research was motivated by the low use of technology-based interactive media in Pancasila Education at elementary schools, especially in Cluster 1 of Lubuk Suhuing District. The media used is still limited to images and internet videos, and the use of Canva is not optimal. This study aims to develop interactive media using Canva based on the Problem Based Learning (PBL) model that is valid, practical, and effective. The research method used is Research and Development (R&D) with the 4D model from Thiagarajan, including Define, Design, Develop, and Disseminate stages. Trial subjects involved material experts, media experts, language experts, two teachers, and fifth grade students from two schools. Instruments used were validation questionnaires, practicality questionnaires, and learning outcome tests. The results showed the media developed obtained a validity score of 86% from material experts, 85% from teachers, and 90% from students, categorized as